Exploring Robert Landy's role method with Christian men along with the social construct of masculinities - Africa, Nolan Glenn (My University, 2021)
This autoethnographic, qualitative research was a self-analysis as well as a look at the roles men play within the constructs of society and Christianity. It looked at the influences that drive our behaviour and questioned which moral grounding forms us, our actions and our thoughts. The research addressed masculinities that make us feel secure, within ourselves, and looked at how we can expand our role repertoire by exploring our counterroles. Therapeutic methods were looked at to see how drama therapy tools can be used for the process of discovering aspects of ourselves that can broaden our current role repertoire. Personal stories were evaluated and related to masculinities, Christianity and society’s construct of how those cultures could be represented in role. Methods on how to expand role repertoire were explored and suggested therapeutic interventions were presented to conclude the research. By exploring self as well as theories on society’s expectations of masculinities and Christian men, I see the role method as an effective introspective means of self-discovery and analysis. This method creates an awareness of self and the roles the self would like to incorporate into the process of becoming a more authentic human being
A research report submitted to the Wits School of Arts (Drama for Life Department) at the University of the Witwatersrand, Faculty of Humanities, in partial fulfilment of the requirements for the degree of Master of Arts in Drama Therapy, 2021